Ending violence against children: What can global agencies do in partnership?. (September 2021) - Raman, Shanti; Muhammad, Tufail; Goldhagen, Jeffrey; Seth, Rajeev; Kadir, Ayesha; Bennett, Sue; D'Annunzio, Danielle; Spencer, Nicholas J.; Bhutta, Zulfiqar A.; Gerbaka, Bernard
Abstract: Globally, the range, scale and burden of all forms of violence against children (VAC) have visibly increased. Yet VAC as a physical, mental, public and social health concern is only recently gaining the prominence it deserves. Addressing VAC is critical. Violence experienced early in life can result in short, medium, long-lasting, and/or even inter-generational negative health outcomes. Ample evidence shows that VAC is widespread and the most common forms are usually perpetrated by people with whom children interact every day in their homes, schools and communities. We report on an innovative collaboration between global agencies, led by the International Society for Social Pediatrics and Child Health (ISSOP), the International Society for Prevention of Child Abuse and Neglect (ISPCAN), and the International Pediatric Association (IPA), who were galvanized to respond to VAC using a child-rights and public health lens. This collaboration led to a position statement on VAC with an implementation plan. The strength of the position statement was the explicit incorporation of a rights-based expansive understanding of VAC, with a description of typologies of violence pertinent to children globally, including child labor, children in armed conflict, trafficking of children and gender-based violence; and the identification of strategies both in preventing violence from occurring and ameliorating the effects in its aftermath. We report on the challenges and successes of our collaborative action at regional and supra-national levels, including opportunistic action.